A comprehensive study on electricity utilization and CO2 emissions in Sami Laris Swalayan, Cilacap, Indonesia - Yuliani, Aulia Rachma; Sari, Mega Mutiara; Suryawan, I Wayan Koko (Universitas Pakuan, 2024)
In today's world, with an increased focus on environmental awareness and sustainability, mitigating carbon footprint has emerged as a crucial goal for businesses across various sectors, including supermarket chains. This research centers on Sami Laris Swalayan, a prominent and widely recognized supermarket chain, to comprehensively analyze its electricity utilization patterns and the corresponding carbon dioxide (CO2) emissions. By delving into electricity utilization data spanning a specific period, this study identifies peak demand periods, explores energy-efficient opportunities, and assesses the potential for integrating renewable energy sources. The research underscores the significance of reducing CO2 emissions, advocating sustainable energy practices within the supermarket chain, contributing to environmental conservation efforts, and fostering a culture of responsible energy management. The investigation begins with a thorough analysis of Sami Laris Swalayan's electricity utilization, seeking to understand the varying trends and patterns in energy consumption. The data above shows the fluctuating electricity consumption of the company, with the highest figure recorded in April, reaching 26,965 kWh. The high electricity usage is attributed to the total operational hours from 09:00 to 21:00 and the addition of other facilities such as the accessory room, bakery outlet, and coffee outlet. In contrast, the lowest consumption was observed in February, with 23,796 kWh, which was influenced by the implementation of Large-Scale Social Restrictions (PSBB) at the end of January 2021. During this period, the operational hours were shortened from 09:00 to 19:00, leading to a decrease in electricity consumption the following month. ABSTRAK Dalam era modern ini, dengan fokus yang semakin meningkat pada kesadaran lingkungan dan keberlanjutan, mengurangi jejak karbon telah menjadi tujuan krusial bagi bisnis di berbagai sektor, termasuk rantai supermarket. Penelitian ini berfokus pada Sami Laris Swalayan, sebuah rantai supermarket yang terkemuka dan dikenal luas, untuk melakukan analisis komprehensif terhadap pola penggunaan listrik dan emisi karbon dioksida (CO2) yang terkait. Dengan menggali data penggunaan listrik selama periode waktu tertentu, penelitian ini bertujuan untuk mengidentifikasi periode permintaan puncak, mengeksplorasi peluang hemat energi, dan menilai potensi integrasi sumber energi terbarukan. Penelitian ini menekankan pentingnya mengurangi emisi CO2 dan mendorong praktik energi berkelanjutan di dalam rantai supermarket, sehingga ikut berkontribusi pada upaya konservasi lingkungan dan menumbuhkan budaya pengelolaan energi yang bertanggung jawab. Penelitian ini dimulai dengan analisis mendalam terhadap penggunaan listrik Sami Laris Swalayan, dengan tujuan untuk memahami tren dan pola variasi dalam konsumsi energi. Data di atas menunjukkan konsumsi listrik perusahaan yang fluktuatif, dengan angka tertinggi tercatat pada bulan April, mencapai 26.965 kWh. Tingginya penggunaan listrik disebabkan oleh total jam operasional dari pukul 09:00 hingga 21:00 dan penambahan fasilitas lain seperti ruang aksesoris, outlet roti, dan outlet kopi. Sebaliknya, konsumsi terendah diamati pada bulan Februari, sebesar 23.796 kWh, yang dipengaruhi oleh penerapan Pembatasan Sosial Berskala Besar (PSBB) pada akhir Januari 2021. Selama periode ini, jam operasional dipersingkat dari pukul 09:00 hingga 19:00, mengakibatkan penurunan konsumsi listrik pada bulan berikutnya.